MOF@MOF core–shell vs. Janus particles and the effect of strain: potential for guest sorption, separation and sequestration - Szilagyi, Petra; Lutz, M.; Gascon, J.; Juan-Alcaniz, J.; Esch, J.; Kapteijn, F.; Geerlings, H.; Dam, B.; Krol, R. (The Royal Society of Chemistry, 2013)
The effect of strain on core-shell MOFcore@MOFshell particles is discussed and compared with that observed for analogous Janus particles. Whereas Janus particles do not display any effect of strain, the core of fully coated core-shell particles collapsed upon the formation of the outer shell, leaving the core inaccessible for guest adsorption. This suggests that Janus particles might become ideal candidates for gas separation, while core-shell particles could play a key role in sequestration of guest molecules.